Assessment of Heavy Metal Contents in Surface Sediment of the Tungguk River Surrounding the Industrial Complex of Gebeng City - Islam, Mir Sujaul; Karim, Md. Abdul; Mohamad Idris, Ali; Noram Irwan, Ramli (Bio Research, 2017)
Gebeng is one of the most important industrial regions in Kuantan, Pahang. The study was conducted in the Gebeng industrial estate to investigate the effect of industrialization on heavy metal concentration in the river tributaries. Sediments were collected from 10 different strategic stations along the river bed. Selected heavy metals were measured by using Inductively Coupled Plasma Mass Spectrometry. Several approaches were used to assess the pollution level of studied sediments. The results revealed that sediments were highly polluted, especially by Co (Contamination factor up to 276.00, Enrichment factor up to 61.00 and Geo-accumulation index up to 55.00) and Hg (CF up to 120.00, EF up to 49.00 and Igeo up to 80.00). The studied heavy metal pollution were ranked as Co> Hg> As> Pb> Zn> Cu> Cr> Cd> Ni>Ba. Based on pollution level sampling stations were classified as 1>10>8>7>9>6>3>2>5>4. This study will help in the river management strategy of the nation through providing updated heavy metals status of the studied sediment.